Production and characterization of different types of malaria pigment (hemozoin) and their potential use for screening for hemozoin inhibiting drugs - Góis, Ana Margarida Ferreira, 1988- (2013)
Tese de mestrado. Biologia (Microbiologia Aplicada). Universidade de Lisboa, Faculdade de Ciências, 2012